Kato-Katz and Lumbreras rapid sedimentation test to evaluate helminth prevalence in the setting of a school-based deworming program. (2nd April 2016) - Lopez, Martha; Morales, Maria Luisa; Konana, Monisha; Hoyer, Paige; Pineda-Reyes, Roberto; White, Arthur Clinton; Garcia, Hector Hugo; Lescano, Andres Guillermo; Gotuzzo, Eduardo; Cabada, Miguel Mauricio
Abstract : The sensitivity of the Kato-Katz test is suboptimal for the evaluation of intestinal helminth prevalence. Moreover, during mass deworming, as helminth egg burden decreases, the sensitivity is likely to decrease. The Lumbreras rapid sedimentation (Lumbreras) is a low-cost non-quantitative test, but may provide useful information in low burden areas. We compared the prevalence of intestinal helminth infections assessed by the Kato-Katz and the Lumbreras rapid sedimentation test on 3 stool specimens from each of 1083 children. The sensitivities were compared using the McNemar paired test. Using the combined outcome of the 3 different stool tests as the standard, Kato-Katz had lower sensitivity than Lumbreras rapid sedimentation tests for Ascaris lumbricoides (85.1% vs. 95.1%, p  = 0.03), Hymenolepis nana (77.7% vs. 97.9%, p  < 0.01), Trichuris trichura (41.7% vs. 100%, p  = 0.01), hookworm (0% vs. 100%, p  = 0.01), and Strongyloides stercoralis (0% vs. 88%, p  < 0.01). Kato-Katz demonstrated significantly lower sensitivity, missing most T. trichiura, hookworm, and S. stercoralis infections. The combination of Kato-Katz and Lumbreras rapid sedimentation tests enables the detection of more intestinal helminths infections in post-deworming low prevalence areas.